ผลการจัดประสบการณ์เรียนรู้สะเต็มศึกษานอกห้องเรียนที่มีต่อทักษะการวัดของเด็กปฐมวัย - Somsuk, Samaporn; Butkatunyoo, Oraphan; Samahito, Chalatip (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2025)
The Effects of Outdoor STEM Education Learning Experience Provision on Young Children’s Measurement Skills Samaporn Somsuk, Oraphan Butkatunyoo and Chalatip Samahito รับบทความ: 5 พฤษภาคม 2568; แก้ไขบทความ: 25 พฤษภาคม 2568; ยอมรับตีพิมพ์: 26 พฤษภาคม 2568; ตีพิมพ์ออนไลน์: 20 มิถุนายน 2568 บทคัดย่อ การศึกษานี้มีวัตถุประสงค์เพื่อศึกษาผลของการจัดประสบการณ์เรียนรู้สะเต็มศึกษานอกห้องเรียนที่มีต่อทักษะการวัดของเด็กปฐมวัย กลุ่มตัวอย่าง คือ เด็กอนุบาลปีที่ 3 จำนวน 30 คน ได้ มาโดยการชักตัวอย่างแบบกลุ่ม เครื่องมือที่ใช้การศึกษาคือแผนการจัดประสบการณ์เรียนรู้สะเต็มศึกษานอกห้องเรียน จำนวน 8 แผน แบบสังเกตและประเมินทักษะการวัดของเด็กปฐมวัย 1 ฉบับ 4 ด้าน ประกอบด้วย การวัดความสูง การวัดความยาว การชั่งน้ำหนัก การตวงปริมาตร เก็บรวบรวมข้อมูลเป็นระยะเวลา 8 สัปดาห์วิเคราะห์ข้อมูลเชิงปริมาณด้วยค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐานและการทดสอบค่าทีและวิเคราะห์ข้อมูลเชิงคุณภาพด้วยการวิเคราะห์เนื้อหา ผลการศึกษาพบว่าเด็กปฐมวัยที่ได้รับการจัดประสบการณ์สะเต็มศึกษานอกห้องเรียนมีค่าเฉลี่ยของคะแนนหลังการจัดประสบการณ์ฯ สูงกว่าก่อนการจัดประสบการณ์ฯ ทั้งโดยรวมและรายด้านอย่างมีนัยสำคัญทางสถิติที่ .05 นอกจากนี้ยังมีการวิเคราะห์เนื้อหาจากบันทึกพฤติกรรมเด็กเพื่อให้ได้ข้อมูลเชิงลึกเกี่ยวกับผลของกิจกรรมการจัดประสบการณ์สะเต็มศึกษานอกห้องเรียน แสดงให้เห็นว่า การจัดประสบการณ์เรียนรู้สะเต็มศึกษานอกห้องเรียนนั้นสามารถพัฒนาทักษะการวัดของเด็กปฐมวัยได้ โดยเด็กสามารถเปรียบเทียบ เรียงลำดับและวัดสิ่งต่าง ๆ โดยใช้หน่วยที่ไม่เป็นมาตรฐานและเป็นมาตรฐานในกระบวนการสร้างชิ้นงานเพื่อแก้ปัญหาในบริบทจริง คำสำคัญ: สะเต็มศึกษานอกห้องเรียน ทักษะการวัด เด็กปฐมวัย Abstract This study aimed to investigate the effects of implementing an outdoor STEM learning experience focused on the development of young children’s measurement skills. The participants were 30 third–year kindergarten children selected through cluster sampling. The research instruments included eight instructional plans designed for providing experiential learning activities outside the classroom, as well as an observation and assessment form of young children’s measurement skills, comprising four domains: height measurement, length measurement, weight measurement, and volume measurement. Data were collected over a period of eight weeks. Quantitative data were analyzed using mean, standard deviation, and t–test, while qualitative data were analyzed using content analysis. The findings indicated that young students who participated in the full–time outdoor STEM learning experience demonstrated a statistically significant improvement in their post–learning experience mean scores at the .05 level, both in overall measurement skills and across individual skill domains. Furthermore, qualitative analysis of behavioral observation records provided in–depth insights into the outcomes of the experiential learning activities. The findings suggest that implementing an outdoor STEM learning experience effectively enhances young children’s measurement skills. This is achieved by engaging young children in activities that promote comparison, sequencing, and measurement using both non–standard and standardized units, within authentic problem–solving contexts that support meaningful learning. Keywords: Outdoor STEM education, Measurement skills, Young children